Special Issue: Activity and Lifestyle Factors in the Elderly: Their Relationship with Degenerative Diseases and Depression - Dillon, Carol (2016)
Much has been written over the ages about the benefits of exercise and physical activity. Marcus Tullius Cicero stated, in _65 BC, that ?It is exercise alone that supports the spirits, and keeps the mind in vigor?. Over the past decade, there has been increasing focus on the influence of a number of lifestyle factors; including: intellectual engagement, social interaction, nutrition, and physical activity; on the cognitive vitality of older adults. Some studies have examined changes in cognition within the normal range, whereas others have asked whether lifestyle factors reduce the risk or delay the onset of age-associated diseases such as Alzheimer?s, Cerebrovascular Disease, or Depression. Physical activity in midlife seems to protect from dementia in old age. Leisure-time physical activity (LTPA) is particularly important due to its broader effects in general and cardiovascular health.This special issue is focused on different aspects of activity: relating physical activity to fragility syndrome, describing the impact of physical activity in the quality of life of elderly patients with cognitive impairment, depression and dementia.